2009
DOI: 10.1177/112067210901900508
|View full text |Cite
|
Sign up to set email alerts
|

Laser in Situ Keratomileusis for Treatment of Fully or Partially Refractive Accommodative Esotropia

Abstract: LASIK is a safe and effective method for treating refractive error and creating orthophoria in fRAE. In pRAE, it eliminates the refractive component of deviation safely and effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…In a previous study, “in patients with RAE, hyperopic LASIK produced orthotropia when there was postoperative emmetropia and in patients with PAE, residual esotropia remained despite a postoperative emmetropia.”[6]…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, “in patients with RAE, hyperopic LASIK produced orthotropia when there was postoperative emmetropia and in patients with PAE, residual esotropia remained despite a postoperative emmetropia.”[6]…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have shown refractive surgery can effectively treat accommodative esotropia [32 ,33-35]. Only a few reports have specifically targeted children and adolescents for refractive surgery to treat accommodative esoptropia [43][44][45]. Phillips et al [45] reported on 15 patients with an average age of 13.9 years old (range:9.1-18.8) with average hyperopia of þ5.35 diopters.…”
Section: Refractive Surgery and Strabismusmentioning
confidence: 98%
“…In myopic and hypermetropic patients with accommodative strabismus, refractive surgical applications have the potential to heal ocular misalignment by correcting refractive errors (7). There are case series with different results for nonaccommodative and partially accommodative deviations (8)(9)(10). It is well known that it is very important to inform the patient about how the deviation will change after refractive surgery.…”
Section: Introductionmentioning
confidence: 99%